Digital health for early psychosis in Ghana: patient and caregiver needs and preferences - Anna Larsen; Joel Agorinya; Alexa Beaulieu; Emmanuel Quame Sottie; Benjamin Buck; Kwadwo Obeng; Bill Kyeremeh; Fredrick Kwame Dogbe; Muhammed Izudeen Iddrisu; Phil Emil Okwei Dowuona; Olivia Oteba Abbey Tetteh; Omari Boakye Emmanuel; et al. (Schizophrenia)
Abstract In West Africa, the long-term consequences of poor early psychosis recovery include poverty, neglect, and community ostracization. To understand the potential for digital health approaches to support early psychosis care in Ghana, we conducted a survey study among early psychosis patients and their caregivers about mental health needs, technology use and access, and interest in digital mental health. Hospital staff at Accra Psychiatric Hospital reviewed hospital medical records from January 2023 - December 2023 identifying young adults (≥18 years old) who had experienced psychosis symptoms for the first time within the prior five years. Trained data assessors contacted these individuals via telephone and invited them and their caregivers to participate; those providing informed consent were interviewed via phone in Twi or English. Overall, 256 individuals participated in the survey, including 121 young adults experiencing early psychosis and 135 caregivers of early psychosis patients. The majority (80%) of early psychosis patients and their caregivers expressed interest in digital mental health for early psychosis and had access to a mobile phone (91%) and necessary mobile infrastructure. Early psychosis patients were most interested in information about managing stress and improving mood via a digital resource (72%). Caregivers desired a digital tool to provide information about psychosis symptoms (86%). Our study among those experiencing early psychosis and their caregivers in Ghana suggests readiness and acceptability of digital mental health for early psychosis care.